ALLELE FREQUENCY OF 19 SNPs IN THE KAZAKH POPULATION - Sikhayeva , N.S.; Iskakova, А.А.; Aitkulova, А.М.; Zholdybayeva, Е.V.; Momynaliev, K.T.; Ramanculov, Е.М. (Eurasian Journal of Applied Biotechnology, 2014)
For understanding genetic predisposition to sports activities it is necessary to pay attention to some genes, such as ACTN3, PPARD, LPL, EDN1, MMP3, INSIG2, PPARGC1A, APOE, SHBG, COL5A1, LEPR, LOXL1, PTPN22, TRAF1. Polymorphisms of these genes are associated with muscular strength, endurance, muscle fiber size and composition. Genetic differences in any of these genes can influence athletic performance. The allele frequency of these genes have been well studied in the European population, but the population of Central Asia has not been extensively studied. It should be noted that the allele frequency may depend on race and ethnicity. The frequency of alleles and genotypes of 19 SNPs were obtained in the Kazakh population (n = 365). The allele frequency (MAF – Minor Allele Frequency) of investigated genes for the Kazakh population were as follows: rs1815739 (С>T) 0,47; rs2016520 (T>C) 0,24; rs328 (C>G) 0,07; rs5370 (G>T) 0,29; rs679620 (С>T) 0,47; rs7566605 (C>G) 0,38; rs8192678 (С>T) 0,52; rs429358 (T>C) 0,14; rs7412 (C>T) 0,05; rs10033464 (G>T) 0,30; rs6258 (C>T) 0,18; rs12722 (C>T) 0,41; rs2025804 (A>G) 0,50; rs2165241 (C>T) 0,38; rs2200733 (C>T) 0,31; rs2476601 (G>A) 0,05; rs3761847 (A>G) 0,48; rs5934505 (T>C) 0,34; rs6457617 (T>C) 0,48.